Monastic Records and the Dissolution: A Tudor Revolution in the Archives?. (July 2016) - Harding, Vanessa
Administrative reform in the 1530s amounted, in Professor Geoffrey Elton's words, to a 'Tudor revolution in government'. The Dissolution of the monasteries and the confiscation of their assets played a major part in this. The need to value, survey, document and exploit the monastic estates transformed government record-keeping, necessitating the creation of new offices – such as the Court of Augmentations – and the adoption of new practices and an expanded bureaucracy. The paper traces the response of the bureaucrats to the challenges to record-management resulting from the Dissolution, and the subsequent history of the monasteries' records of landholding, a task complicated by the activities of later government archivists.